1972
DOI: 10.1037/h0033193
|View full text |Cite
|
Sign up to set email alerts
|

Didactic, experiential, and modeling factors in the learning of empathy.

Abstract: Effects of audio modeling versus no modeling and of experiential supervision versus didactic supervision were examined in brief empathy training. Three supervisors had six trainees in each of four groups: modeling-didactic supervision, no-modeling-didactic supervision, modeling-experiential supervision, no-modeling-experiential supervision. Two groups of 12 each received no supervision: modeling-controls and no-modeling-controls. Subject responses to recorded client statements indicated significant training ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

1975
1975
1993
1993

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 16 publications
2
43
0
1
Order By: Relevance
“…Since some students chose to extend their projects beyond the minimum time, treatments varied from three ro nine weeks For data analysis, average scores for the baseline week and the final week were used to y~e l d a pre and a post score for each student Pre-post Empathy Test. Paper and pencil forms of a situation test used in prior training studies (Payne, Note 1;Payne & Gralinski, 1968;Payne, Weiss. & Kapp, 1972;Payne, Winter, & Bell, 1972) were administered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since some students chose to extend their projects beyond the minimum time, treatments varied from three ro nine weeks For data analysis, average scores for the baseline week and the final week were used to y~e l d a pre and a post score for each student Pre-post Empathy Test. Paper and pencil forms of a situation test used in prior training studies (Payne, Note 1;Payne & Gralinski, 1968;Payne, Weiss. & Kapp, 1972;Payne, Winter, & Bell, 1972) were administered.…”
Section: Methodsmentioning
confidence: 99%
“…measure have rndicated no improvement for subjects not Helping Skills. Scores on the empathy test using Carkreceiving training (Hodge, 1976;Payne, Weiss, & Kapp, 1972;Payne, Winter. & Bell.…”
Section: Methodsmentioning
confidence: 99%
“…Nor has empirical evidence yet been reported to conclusively demonstrate that any such rating scale is validly related to any specific therapist behaviors, to the client's perception of the therapist's effectiveness, or to any other validated measure of therapist performance. This limitation applies even to the most frequently utilized (e.g., Carkhuff & Truax, 1965;Carlson, 1974;Gormally, Hill, Gulanick, & McGovern, 1975;Jordan, 1969;McWhirter, 1974;Payne, Weiss, & Knapp, 1972;Toukmanian & Rennie, 1975) and best researched (Carkhuff, 1969;Truax & Carkhuff, 1967) rating scales for observers, the accurate empathy, nonpossessive warmth, genuineness, and concreteness measures (Gurman, 1978;Mitchell, Bozarth, & Krauft, 1978). The Counselor Verbal Response Scale (CVRS) (e.g., Austin & Alterkruse, 1972;Dendy, 1972;A.…”
Section: Observer Frequency Counts and Ratingsmentioning
confidence: 96%
“…Most of these (Payne and Gralinski, 1968;Birk, 1972;Payne, Weiss and Kapp, 1972;Payne, Winter and Bell, 1972;and Carlson, 1974) have found the didactic to be more effective than the experiential in the learning of empathy. On the other hand, Silverman (1972Silverman ( , 1973 found that the experiential approach was more successful in fostering our affective relationships, as perceived by the counselor trainees and their clients.…”
Section: Introductionmentioning
confidence: 99%